To Own or Not to Own? Household Portfolios, Demographics and Institutions in a Cross-National Perspective - Eva Sierminska; Karina Doorley (Institute for the Study of Labor (IZA), 2013)
Using harmonized wealth data and a novel decomposition approach, we show that cohort effects exist in the income profiles of asset and debt portfolios for a sample of European countries, the U.S. and Canada. We find that younger households' participation decisions in assets are more responsive to income than older households. Family structure plays a significant role in explaining cross-country differences for both cohorts. Examining institutional differences, we find that in more financially developed and economically open countries, households are less likely to own housing but more likely to be in debt. Typical mortgage characteristics and mathematical literacy are also correlated with debt participation across countries. These findings have important implications for policy setting during times of financial unease for the young, as well as for the future in helping secure adequate income for the elderly. Our results show that there is scope for policies which promote asset participation for young households and debt participation, where there is a need for consumpation smoothing, for older households.
Keywords: G11; G21; J10; 330; wealth portfolios; decomposition; institutions; demographics